Facilities Complaints and Evaluations System for Kolej Kerawang UiTM Kuala Terengganu (e-CEK) / Faten Anis Azreen Zakaria - Zakaria, Faten Anis Azreen (2017)
Facilities Complaints and Evaluations system for Kolej Kerawang (e-CEK) is a system that being developed for Unit Pengurusan Kolej Kerawang (UPKK). This system enable user to manage information of facilities complaints and evaluations in a systematic way. Currently, all the facilities complaints and evaluations are conducting manually that requires student to fill in the form, submit the form to the college staff and college staff need to approve the complaints. Then, college staff will contact staff of Bahagian Pengurusan Fasiliti (BPF) for further action. With the increasing number of students, the manual process is time consuming and need a lot of book usage to record the complaint information. This system will enhance the flow of current process and facilitate user in handling the complaints and evaluation task. Adapted Waterfall Model is used for development of e-CEK which contains five phases that need to be followed. The five phases are planning, analysis, design, development and testing and evaluation. Other than that, User Centered Design (UCD) are implemented in this system development which is involve the user directly in each phase. Functionality testing is conducted by the developer and tester by using the test plan based on stated requirements. In term of usability, the system is evaluated by three experts and thirty respondents. Six constructs were used in the evaluation process that consists of ease of use, user interface, user experience, consistency and satisfaction. Overall, the highest mean is satisfaction construct (Mean=4.53, SD=0.57). For future enhancement, it is recommended that this system to have a notification module where notification via short message system (SMS) for the technician to be alerted that they have been assigned for a new task.